Impact of Soybean Cyst Nematode Resistance on Soybean Yield. Issue 3 (16th June 2017) - Rincker, Keith; Cary, Troy; Diers, Brian W.
Abstract : Soybean cyst nematode (SCN) ( Heterodera glycines Ichinohe) of soybean [ Glycine max (L.) Merr.] causes extensive yield loss, and host resistance has been an effective strategy to minimize this loss. However, shifts in SCN population virulence compatibility have resulted from the extensive use of PI 88788 as a source of resistance in the northern United States. The Northern Regional Soybean Cyst Nematode Tests offer a vast amount of yield testing, combined with resistance screening of entries and the characterization of the SCN infection of test fields. The objectives of this study were to use regional test results (i) to quantify the impact of resistance as the initial field SCN egg counts increase, (ii) to explore effects of maturity group (MG) on resistance, and (iii) to gain insights into how the ability of SCN to infect germplasm with resistance from PI 88788 affects yield. Yield tests across 11 yr were combined into a single dataset with over 1247 test–environment combinations. Analysis of these data showed that the yield advantage of SCN resistant entries increased as initial egg counts increased, and a larger advantage was found in early MGs (00–II) than in later MGs (III–IV). A yield advantage was documented at environments with an initial egg count as low as 100 eggs 100 cm −3 soil. At the levels of SCN infection on PI 88788 found in infested locations, breeding lines with resistance from PI 88788 yielded more than susceptible entries. Analysis of this dataset offers a unique view of the impact SCN resistance provides to soybean.